Exploring the Application of Aromatherapy in Junior High School English Language Teaching - Yao, Yanying; Yang, Xinyi; Teng, Jiang (Journal of Educational Research and Policies, 2025)
This study explores the impact of aromatherapy on junior high school English language teaching by diffusing four essential oils in an eighth-grade classroom for two months. Student reflections gathered after the experiment are discussed through discourse analysis, demonstrating that aromatherapy contributes to improved concentration, retention, and engagement among the majority of students. The findings underscore the potential of aromatherapy as a complementary tool in education, providing valuable insights into the role of sensory interventions in optimizing learning environments. Guidelines are proposed to ensure its safe and effective application, emphasizing the importance of using pure and natural essential oils and controlled concentrations. This study presents a novel approach to integrating sensory-based strategies into conventional educational practices, offering new avenues for enhancing the academic performance of junior high school students.